A micro-controller controlled 3 Axis CNC Machine for engraving and designing - Khan, Tanzim Ahmed; Samiu, Mohammad Samiul Haque; Sani, Md. Shahabuddin; Haque, Md. Mozammel (BRAC University, 2018)
This thesis report is submitted in partial fulfilment of the requirements for the degree of Bachelor of Science in Electrical and Electronic Engineering, 2017.